The effect of a support program based on the psychosocial needs of the family on the family care burden of ischemic heart patients: a systematic review study. - Gashmard, Roqayeh; Hasanpour, Esmat; Daman, Shima; Amini, Parivash Hafez; Sefidi, Maryam Jamshidian Ghale; Ladani, Fatemeh Kafami; bagherieh, Molood; Nabizadeh, Mohammad (Revista Latinoamericana de Hipertensión, 2024)
Introduction: Heart disease can have debilitating physical and mental consequences that can affect the care behavior of the elderly. The aim of study was the effect of a support program based on the psychosocial needs of the family on the family care burden of ischemic heart patients. Methods: Science Direct, Pub Med, Google Scholar, SID, MagIran databases were reviewed and electronic data were used to identify the psychosocial needs of the family on the burden of family care of heart patients. In the initial search, 824 articles were obtained, of which 379 duplicate articles were removed. Considering the inclusion and exclusion criteria, the number of articles was reduced to 445 articles. Finally, 10 articles were included in study. Results: A total of 824 articles were screened, which led to the selection of 11 studies that met the inclusion criteria and were included in study. Some studies defined caregivers as family caregivers. Five studies focused on life partners and caregivers of patients. Some studies generally defined caregivers as someone identified by the patient as a caregiver. Conclusion: Providing a training program about the different dimensions of support that family caregivers need reduces the perceived stress of family caregivers of cardiac patients.